Can the reading load be engaging? Connecting the instrumental, critical and aesthetic in academic reading for student learning - Nguyen, Ha Thi Thu; Henderson, Ariana (Journal of University Teaching and Learning Practice, 2020)
Learning an academic discipline requires at a fundamental level reading of knowledge that has been recorded, debated and developed in writing over time. Given the essential role of reading in shaping knowledge, there needs to be more emphasis on approaches that nurture an engaged reading practice. This article explores the role of instrumental, critical and aesthetic reading stances in engaging students in academic reading at university and the extent to which connecting these reading stances can enhance student learning through academic reading. Using this dynamic view of reading, the article examines insights and evidence from recent research to investigate the connection between these reading stances and student learning. The studies analysed indicate elements of instrumental, critical and aesthetic reading in approaches that effectively engage learners in academic reading. These ways of reading are linked to enhanced learning in terms of individual reflexivity, disciplinary participation, social perspective and global awareness. An analysis of the studies investigated advocates for using a variety of text types, giving students choice of texts, explicitly teaching dynamic reading skills, providing opportunities for social reading practices and implementing process-based assessments for learning. These practices can lighten the academic reading load by enhancing engagement and learning of disciplinary knowledge.